2004
DOI: 10.1002/jcp.20045
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of the epidermal growth factor receptor‐tyrosine kinase by ZD1839 (‘Iressa’) induces cell‐cycle arrest and inhibits proliferation in prostate cancer cells

Abstract: The epidermal growth factor (EGF) plays a role in the development of prostate cancer, which becomes essential after androgen resistance has emerged. The EGF receptor (EGFR) is therefore a potential target for anticancer therapy. We evaluated the effects of ZD1839 ('Iressa'), an orally active EGFR-tyrosine kinase inhibitor, on prostate cancer cell lines. The effects of ZD1839 were evaluated on the anchorage dependent and independent growth of androgen-responsive (LNCaP) and androgen-independent (DU145 and PC3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
38
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 30 publications
8
38
0
1
Order By: Relevance
“…Immunoblot analysis was performed with the anticyclin D1 monoclonal antibody (Santa Cruz Biotechnology) according to the manufacturer's instructions. Data are representative of two independent experiments a recent study, it was similarly shown that an EGFR tyrosine kinase inhibitor, ZD1839 (Iressa), blocked G 0 /G 1 to S cell cycle progression of PC-3, DU145, and LNCaP prostate cancer cell lines (Sgambato et al, 2004). However, in this study it was also shown that ZD1839 treatment did not affect cyclin D1 expression.…”
supporting
confidence: 47%
“…Immunoblot analysis was performed with the anticyclin D1 monoclonal antibody (Santa Cruz Biotechnology) according to the manufacturer's instructions. Data are representative of two independent experiments a recent study, it was similarly shown that an EGFR tyrosine kinase inhibitor, ZD1839 (Iressa), blocked G 0 /G 1 to S cell cycle progression of PC-3, DU145, and LNCaP prostate cancer cell lines (Sgambato et al, 2004). However, in this study it was also shown that ZD1839 treatment did not affect cyclin D1 expression.…”
supporting
confidence: 47%
“…We also provide evidence for a similar requirement for PKCa in the phorbol ester -induced Erk1/2 activation response of an unrelated androgen-independent human prostate cancer cell line, DU145, which expresses the same PKC isozymes as PC-3 and is also Iressa-sensitive (3,22). Sn-1,2-diacylglycerol, the endogenous PKC-activating homologue of TPA, is present at elevated levels in transformed cells (29,30), and may serve as the pathophysiologic counterpart of acute TPA treatment by sustaining a moderate level of PKCa stimulation that in turn sustains EGFR transactivation in prostate cancer cells in vivo.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, a similar analysis of human prostate cancer tumors corresponding to different clinical disease stages established that EGFR expression significantly increases in neoplastic epithelial cells with disease progression and is predictive of relapse following radical prostatectomy (2). The importance of EGFR-dependent autocrine signaling to prostate cancer cell growth and survival is reflected in the negligible growth stimulation achieved by treatment of cultured human prostate cancer cells (androgen-dependent LNCaP and androgen-independent PC-3 and DU145 cells) with EGFR ligands despite the pronounced growth suppression achieved with the selective EGFR-inhibitor Iressa (gefitinib), which arrested the cells in G 1 (3). Likewise, Iressa suppressed the development of androgendependent human CWR22 prostate cancer tumors in nude mice and was even more effective against tumors formed by CWR22 sublines with attenuated androgen dependence (4).…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous p27 overexpression results in cell cycle regulation and an increase in cell apoptosis in human prostate carcinoma cell lines [5]. In addition, some studies have shown that EGF-induced stimulation of growth in prostate cancer cells is associated with downregulation of p27 [6,7]. Based on these theories, we hypothesized that the antitumour action of CDKI p27 may be through the EGF signalling pathway in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 96%